2009
DOI: 10.1007/978-0-387-85998-9_4
|View full text |Cite
|
Sign up to set email alerts
|

Blood Vessel Specific Vaso-Activity To Nitrite Under Normoxic And Hypoxic Conditions

Abstract: This study uses an organ chamber bioactivity assay to characterise the direct effect of sodium nitrite upon rabbit blood vessels (aorta (Ao), inferior vena cava (IVC) and pulmonary artery (PA)) in a haemoglobin independent/variable oxygen environment. In 95% oxygen constriction to 8g (Ao), 6g (PA) and 4g (IVC) was achieved using 1 microM phenylephrine. The same constriction in 1% oxygen required 3 microM. During 95% oxygen constriction was consistent and sustained for all vessels. However under 1% oxygen PA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…Under normoxic conditions, the pulmonary artery dilated more than the aorta (the inferior vena cava response was variable). However, under conditions of hypoxia, dilatation of the aorta was significantly greater than of the pulmonary artery and the inferior vena cava . The dilatory response during hypoxia was enhanced in all vascular beds.…”
Section: Cardiovascular Effects Of Nitrate and Nitritementioning
confidence: 84%
“…Under normoxic conditions, the pulmonary artery dilated more than the aorta (the inferior vena cava response was variable). However, under conditions of hypoxia, dilatation of the aorta was significantly greater than of the pulmonary artery and the inferior vena cava . The dilatory response during hypoxia was enhanced in all vascular beds.…”
Section: Cardiovascular Effects Of Nitrate and Nitritementioning
confidence: 84%
“…It has been shown that even in the absence of added heme, nitrite induces vasorelaxation at high and low oxygen tensions via NO formation [21; 22; 48; 49]. As a result, the addition of either bHb or THb would be expected to lead to inhibition of nitrite-dependent responses.…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28] Therefore, it is possible that the Ru-NO + donates NO, whereas the configuration Ru-NO 2 2 may donate NO 2 2 or generate NO. [26][27][28] Therefore, it is possible that the Ru-NO + donates NO, whereas the configuration Ru-NO 2 2 may donate NO 2 2 or generate NO.…”
Section: Discussionmentioning
confidence: 99%